A systematic literature review of artificial intelligence in the healthcare sector: Benefits, challenges, methodologies, and functionalities - Omar Ali; Wiem Abdelbaki; Anup Shrestha; Ersin Elbasi; Mohammad Abdallah Ali Alryalat; Yogesh K. Dwivedi (Journal of Innovation & Knowledge (JIK), 2023)
Administrative and medical processes of the healthcare organizations are rapidly changing because of the use of artificial intelligence (AI) systems. This change demonstrates the critical impact of AI at multiple activities, particularly in medical processes related to early detection and diagnosis. Previous studies suggest that AI can raise the quality of services in the healthcare industry. AI-based technologies have reported to improve human life quality, making life easier, safer and more productive. This study presents a systematic review of academic articles on the application of AI in the healthcare sector. The review initially considered 1,988 academic articles from major scholarly databases. After a careful review, the list was filtered down to 180 articles for full analysis to present a classification framework based on four dimensions: AI-enabled healthcare benefits, challenges, methodologies, and functionalities. It was identified that AI continues to significantly outperform humans in terms of accuracy, efficiency and timely execution of medical and related administrative processes. Benefits for patients' map directly to the relevant AI functionalities in the categories of diagnosis, treatment, consultation and health monitoring for self-management of chronic conditions. Implications for future research directions are identified in the areas of value-added healthcare services for medical decision-making, security and privacy for patient data, health monitoring features, and creative IT service delivery models using AI.
Keywords: Z00; Z1; 650; Artificial intelligence; Healthcare; Technology challenges; Systematic literature review; Technology benefits